2021
DOI: 10.1186/s10020-021-00269-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of vanoxerine dihydrochloride as a CDK2/4/6 triple-inhibitor for the treatment of human hepatocellular carcinoma

Abstract: Background Cyclin-dependent kinases 2/4/6 (CDK2/4/6) play critical roles in cell cycle progression, and their deregulations are hallmarks of hepatocellular carcinoma (HCC). Methods We used the combination of computational and experimental approaches to discover a CDK2/4/6 triple-inhibitor from FDA approved small-molecule drugs for the treatment of HCC. Results We identified vanoxerine dihydrochloride a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Briefly, cells to be tested were plated at an initial density of 1 × 10 4 cells/well per 100 μL of cell culture medium in 96-well plates; 10 μL of CCK-8 reagent was added into 100 μL of cell culture medium. The optical density (OD) values were measured at 450 nm using a microplate reader [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, cells to be tested were plated at an initial density of 1 × 10 4 cells/well per 100 μL of cell culture medium in 96-well plates; 10 μL of CCK-8 reagent was added into 100 μL of cell culture medium. The optical density (OD) values were measured at 450 nm using a microplate reader [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protein concentration was measured using the BCA method following the manufacturer’s protocol. Then, equal amount proteins (15 μg/sample) were loaded and separated on 10% SDS-PAGE, transferred to PVDF membrane, blocked with 5% fat free milk, blotted with primary antibody (antibody against CDKN1A at 1:2000, antibody against Ki-67 at 1:200 or antibody against GAPDH at 1:1000) at 4°C overnight and secondary antibody at room temperature for 1 h, respectively, developed with SuperSignal Chemiluminescent HRP Substrate, and photographed with software Image Lab version in ChemiDoc MP Imaging System (Bio-Rad, USA) [ 11 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CDK2 in cyclin, as an essential component of cell cycle mechanism, can form CDK2/cyclin E complex with cyclin E, and it is mainly active CDK2/cyclin A complex and phosphorylated E2F in the S phase of the cell cycle and remains in the nucleus in the form of CDK2 in G2 phase. A previous study revealed that phytochemicals could target the CDK2 to treat HCC (48). PDCD4, also known as a programmed cell death protein, participates in the apoptotic signaling pathway and acts as an inhibitor of tumorigenic transformation.…”
Section: Discussionmentioning
confidence: 99%